We have the two functions h(x) = x^3+ x and g(x) = 2x + 3.

Now we need to find g(h(2)).

h(2) = 2^3 + 2

= 8 + 2

= 10

g(h(2))

= g(10)

= 2*10 + 3

= 20 + 3

= 23

**Therefore g(h(2)) = 23.**

Posted on

Given that:

h(x) = x^3 + x

g(x) = 2x+ 3

We need to find g(h(2))

First we will determine the values of h(2).

==> h(2) = 2^3 + 2 = 8+2 = 10

Now we will substitute into g(h(2)

==> g(h(2)) = g(10)

Now we will substitute into g(x).

==> g(10) = 2*10 + 3 = 23

**==> g(h(2)) = 23**

Posted on

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now